SIÇANLARDA AKUT VE KRONİK NİTRİK OKSİT SENTAZ İNHİBİSYONU KAN BASINCI VE PLAZMA NİTRİK OKSİT İLİŞKİLERİ VE ELEKTROKİMYASAL VE SPEKTROFOTOMETRİK YÖNTEMLERİN KARŞILAŞTIRILMASI - YILMAZ, ENGİN (Fırat Üniveristesi, 2005)
Nitrik oksit sentaz (NOS) inhibisyonu sonucu oluşan kan basıncı (KB) artışlan ve plazma NO değerleri değişimleri arasındaki ilişkiler henüz açıkça belirlenmemiştir. Bu çalışmanın amacı; 1) normal ve NOS enzim inhibitörü N

The relationship between the nitric oxide synthase (NOS) inhibition mediated blood pressure (BP) elevation and changes in plasma nitric oxide (NO) levels is not determined yet. Aims of this study were 1) to determine BP and plasma NO levels in normal and the NOS inhibitor No Nitro-L-arjinin (L-NNA) administered rats and evaluate the relationship between the changes in BP and NÛ2'+ NO3" (NOx) levels and 2) to compare the results of NO level measusements obtained by spectrophotometer and NO meter. Adult male Wistar rats were divided into four groups: First group served as controls (n=10). 2) Rats in the acute dose of L-NNA main group (aL-NNA, n=19) were administered a single dose of L-NNA (25 mg/kg i.p.) and BP were measured 1 hour 3 hour and 24 hour, later respectively and blood samples were collected. 3) Animals in the chronic low dose of L-NNA main group (1L-NNA, n=19) were administered L-NNA (~16 mg/kg in drinking water) for 2 weeks and after final dose, BP was measured immediately after the final dose, 24 hours and 48 hours after and blood samples were also collected. 4) Chronic high dose of L-NNA group (hL-NNA) was given L-NNA as 47 mg/kg/day in drinking water for 2 week (n=28), and after the final dose, BP was immediately measured and blood samples obtained. In chronic low dose and chronic high dose groups, BP measured before L-NNA administration and 7th and 14th days after L-NNA administration with tail-cuff method, respectively. In 1L-NNA and hL-NNA groups, while BP and plasma NOx levels significantly higher on the day 14, NOx levels significantly lower 24 and 48 hours after administration of L-NNA in the dL-NNA group. In aL-NNA main group, single doseL-NNA administration, while BP increased at 1 and 3 hours, plasma NOx levels significantly reduced 3 hours following the drug administration. After 24 hours, both BP and NOx levels were recovered. There was no significant difference between the values of NOx measured with spectrophotometer and NO meter. Key words:L-NNA, Blood pressure, Plasma NOx, Spectrophotometer, NO meter,
The relationship between blood pressure changes and plasma nitric oxide levels in acute and chronic nitric oxide synthase inhibition in rats and the compharison of the electrochemical and spectrophotometric methods
Keywords: Eczacılık ve Farmakoloji